2016
DOI: 10.1080/23802359.2016.1197057
|View full text |Cite
|
Sign up to set email alerts
|

Complete plastid genome of Astragalus membranaceus (Fisch.) Bunge var. membranaceus

Abstract: The complete nucleotide sequence of the Astragalus membranaceus (Fisch.) Bunge var. membranaceus chloroplast genome was reported and characterized in this study. The chloroplast genome is a circular molecule of 123623 bp that belongs to the inverted repeat-lacking clade (IRLC). It comprises 110 genes, including 76 protein-coding genes, four unique rRNAs and 30 tRNAs. Similar to the plastomes of A. membranaceus (Fisch.) Bunge var. mongholicus (Bunge) P. K. Hsiao and other closely related species, rpl22 and rps1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The application of plant remedies, particularly, Astragalus species seem to be one of the promising alternatives (Griggs & Jacob, ). Astragalus membranaceus is a leguminous plant from the two main varieties; Astragalus membranaceus (Fisch) Bunge variety mongholicus (Bunge) Hsiao and Astragalus membranaceus (Fisch) Bunge (Wang et al., ). Dried Astragalus roots contain chemical compounds such as alkaloids, polysaccharides, glycosides, flavonoids, amino acids, saponins, and trace mineral which exhibit both medicinal and nutritional characteristics (Xi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of plant remedies, particularly, Astragalus species seem to be one of the promising alternatives (Griggs & Jacob, ). Astragalus membranaceus is a leguminous plant from the two main varieties; Astragalus membranaceus (Fisch) Bunge variety mongholicus (Bunge) Hsiao and Astragalus membranaceus (Fisch) Bunge (Wang et al., ). Dried Astragalus roots contain chemical compounds such as alkaloids, polysaccharides, glycosides, flavonoids, amino acids, saponins, and trace mineral which exhibit both medicinal and nutritional characteristics (Xi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of antibiotic‐resistant strains among many pathogenic microorganisms and consumer requirement for organic food products has triggered the search for an alternative approach to control microbial infection in pigs (Adams et al, ; Che et al, ). The supplementation of various plant extracts in animal studies or in vitro studies has served as a promising alternative to antibiotic use (Che et al, ; Pan et al, ; Wang et al, ; Zhao et al, ). Understanding how these plant extracts modify the gastrointestinal milieus and nutritional requirements of pigs (Skjolaas, Burkey, Dritz, & Minton, ) and other animals is vital.…”
Section: Discussionmentioning
confidence: 99%
“…supplementation of various plant extracts in animal studies or in vitro studies has served as a promising alternative to antibiotic use(Che et al, 2018;Pan et al, 2017;Wang et al, 2016;Zhao et al, 2014).Understanding how these plant extracts modify the gastrointestinal milieus and nutritional requirements of pigs(Skjolaas, Burkey, Dritz, & Minton, 2007) and other animals is vital. Early weaning of piglets is a common husbandry practice in most commercial pig farms(Adams et al, 2018(Adams et al, , 2019, pigs during this condition has less developed gastrointestinal tracts(Chen et al, 2017) and reduce immunological protections, leading to the increase in disease susceptibility and infections by enteric bacteria(Adams et al, 2018;Kick, Tompkins, Flowers, Whisnant, & Almond, 2012).…”
mentioning
confidence: 99%
“…Flavonoids are the largest group of polyphenolic compounds isolated from AR, accounting for 4.34% ethanol extract of AR ( Xu et al, 2013 ). Up to now, studies have reveal that several subclasses of flavonoids from been identified from AR, such as quercetin, calycosin, formononetin, sphaemphyside SB, isomucronulatol, formononetin-7-O-β-D-glycoside, methylnissolin, (6aR, l 1aR) 9,10-dimethoxypterocarpan-3-O-β-D-glycoside, 7,2′-dihydroxy-3′,4′-dimethoxy-isoflavane-7-O-β-D-glycoside ( Zhang et al, 2012 ; Wang B et al, 2016 ). Biological activities of flavonoids vary between each other because of their differences in action mode, and bioavailability ( Ullah et al, 2020 ).…”
Section: Potential Mechanisms Underlying the Therapeutic Effect Of Bi...mentioning
confidence: 99%